Strategi Promosi Endorsement oleh Digital Influencer dalam Etika Bisnis Islam - Ayuningtyas, Felicia Neva (Universitas Negeri Surabaya, 2021)
Promotions by means of endorsements are widely used in this digital era to inform consumers of products. Endorsement activities with services from digital influencers were chosen because they have a big impact on influencing their followers. In it’s application, endorsement activities are still found that are not in accordance with the principles of promotion according to Islamic business ethics. This research aimed to find out how digital influencers do endorsement according to Islamic business ethics. This research uses a qualitative method with a descriptive approach. Techniques used to collect datain this research are interviews, observation, and documentation. The results stated that some ethics are not applied by influencers when doing endorsement, namely covering their part of body, delivering promotion transparently, and not requiring halal labels when promoting food.